Breaking his Spell: Rewriting the Mythic Female Body in Intan Paramaditha’s Apple and Knife - Gonzales, Gema Charmaine (SARE: Southeast Asian Review of English, 2020)
Numerous are the patrilineal mythic narratives that institutionalize unidimensional representations of women, portraying female bodies either as repositories of submission and passivity or as cesspools of chaos and corruption. Through insidious reproduction, such myths cast a discursive spell that dispossesses women of their subjectivity and agency. To break this curse and regain their voice, feminist authors have undertaken the task of rewriting old myths in ways that speak to current local problématiques. Intan Paramaditha’s collection of stories, Apple and Knife (2018), is exemplary of this mission: in her speculative quill, fairy tales become reports of female body policing, vampires are symbolic of non-normative roles and a menstruation-eating monster is a counter-metaphor to misogynist scatological taboos. With a framework informed by feminist and postmodernist studies, this article explores the stylistic modes of corporeal writing in revisionist mythmaking. How are female bodies recast in revised myths in the interest of subverting standards of femininity? How does speculative fiction serve as an effective instrument in celebrating bodies symptomatically silenced in “original” texts? By fostering a dialogue between corporeal writing and revisionist speculative fiction, this paper examines how the female body may be reimagined outside what is deemed singular, natural, or authentic, both in terms of genre and gender.